2021
DOI: 10.1177/15459683211006713
|View full text |Cite
|
Sign up to set email alerts
|

Resting State Connectivity Is Modulated by Motor Learning in Individuals After Stroke

Abstract: Objective Activity patterns across brain regions that can be characterized at rest (ie, resting-state functional connectivity [rsFC]) are disrupted after stroke and linked to impairments in motor function. While changes in rsFC are associated with motor recovery, it is not clear how rsFC is modulated by skilled motor practice used to promote recovery. The current study examined how rsFC is modulated by skilled motor practice after stroke and how changes in rsFC are linked to motor learning. Methods Two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…This idea is supported by prior work that showed that after stroke individuals rely on a dispersed functional network to learn as compared to age-matched controls. 47 Both the current study of brain myelination, and our past work of functional connectivity, 47 suggest that the motor cortex and regions in the parietal cortex interact to support motor learning after stroke. These interactions are not surprising given the need for parietal cortical function, which supports visuomotor integration during reaching movements, for motor task success.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This idea is supported by prior work that showed that after stroke individuals rely on a dispersed functional network to learn as compared to age-matched controls. 47 Both the current study of brain myelination, and our past work of functional connectivity, 47 suggest that the motor cortex and regions in the parietal cortex interact to support motor learning after stroke. These interactions are not surprising given the need for parietal cortical function, which supports visuomotor integration during reaching movements, for motor task success.…”
Section: Discussionmentioning
confidence: 79%
“…After stroke, functional connectivity shifts to nearby networks not immediately impacted by the lesion. 47 Though the corticospinal tract may be important for motor recovery, 18,48 it is likely that individuals with damage to the CST who are in the chronic stage of stroke recovery (>6 months post) employ alternate pathways to support limb motor function. Therefore, in the current study of individuals with chronic stroke, we broadened the inclusion criteria to cover regions that could possibly be affected by the stroke beyond those traditionally studied, including association fibers and sensorimotor regions.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment effect itself was positively associated with the coupling strength between left angular gyrus and left M1. 66 As a consequence, future studies will have to acknowledge that precise characteristics of experimental setups, motor task or training paradigms as well as outcome measures have a relevant influence on brain–behaviour associations, whether causal or not. An overview of functional and effective connectivity studies is given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven (N = 27) neurologically intact, older adult participants (mean age ± standard deviation: 64.2 ± 8.5 years, 2 left-hand dominant, 17 females, female mean age ± standard deviation: 62.8 ± 8.0 years, male mean age ± standard deviation: 66.7 ± 8.3 years) completed a 10-session (4 week) complex visuo-motor training task. Task specifics are provided in Kraeutner et al 91 . Briefly, participants engaged in a semi-immersive virtual reality-based intercept and release task (TRack And Intercept Task; TRAIT) that was presented on a 46-inch monitor, viewed at 72 inches away (screen refresh rate 59 Hz).…”
Section: Methodsmentioning
confidence: 99%